Does Feedback from Physical Activity Measurement Devices Influence Physical Activity? Evidence From a Randomized Controlled Trial - Htay-Wah Saw; Arie Kapteyn; Jill Darling (Survey Research Methods)
Wearable electronic devices are increasingly used to collect physical activity (PA) data. Most wearables provide PA feedback to users. The feedback has the potential for biasing measurements as users may increase their PA level in response to the feedback. On the other hand, the feedback can also be a desirable property as it can be employed to promote PA across settings. Studies examining the causal feedback effect independent of other factors have been limited. This study analyzed the causal effect of PA feedback provided by wearables. We implemented 4 field experiments over a period of 8 months. We recruited participants from a probability-based internet panel and asked them to wear continuously: (i) a PA device that does not provide feedback for 7 consecutive days, (ii) a PA device that provides feedback for another 7 consecutive days, (iii) both devices for another 1 or 2 consecutive days. After 6 PM each experimental day, participants completed a short online survey asking them about their experiences participating in the study. Of 120 eligible participants assessed, 81 provided valid and complete data and 39 were lost to follow-up. Participants with valid and complete data (n=81) accumulated 7% more PA on a given day when they wore a PA device providing feedback relative to when they wore a PA device that does not provide feedback (p-value<0.001). The feedback effect was robust to the inclusion of additional factors that might influence PA. Use of research-grade PA devices that provide no feedback is warranted for studies whose primary goals are to collect population PA data with minimal measurement errors, while wearables with feedback are most suited for PA intervention studies. When using PA devices that provide feedback, one needs to be aware of the bias that may result.